2020
DOI: 10.1186/s12879-020-05366-z
|View full text |Cite
|
Sign up to set email alerts
|

Association of HIV infection with clinical and laboratory characteristics of sickle cell disease

Abstract: Background: Sickle cell disease (SCD) is a multisystem disorder characterized by a wide spectrum of clinical manifestations and severity. Studies investigating potential effects of co-morbid human immunodeficiency virus (HIV) and SCD have produced conflicting results, and additional investigations are needed to elucidate whether the interaction between the two disease states might impact both HIV and SCD clinical outcomes. The association of HIV infection with clinical and laboratory characteristics of patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
(54 reference statements)
0
1
0
Order By: Relevance
“…HIV infection also creates a favorable environment for pneumococcal infection, which can be fatal, resulting in severe pneumonia or meningitis in SCD adults [138]. A nested case-control study by Belisário et al showed that HIV infection increased the severity of SCD-related symptoms such as ACS/pneumonia, sepsis/bacteremia, pyelonephritis, ischemic stroke, hemorrhagic stroke, abnormal transcranial doppler, and pulmonary hypertension [139]. Furthermore, National Hospital Discharge Survey data in the period of 1997-2009 showed that SCD is associated with decreased HIV but higher HBV and HCV co-morbidities in adult African-Americans [140].…”
Section: Hiv Infectionsmentioning
confidence: 99%
“…HIV infection also creates a favorable environment for pneumococcal infection, which can be fatal, resulting in severe pneumonia or meningitis in SCD adults [138]. A nested case-control study by Belisário et al showed that HIV infection increased the severity of SCD-related symptoms such as ACS/pneumonia, sepsis/bacteremia, pyelonephritis, ischemic stroke, hemorrhagic stroke, abnormal transcranial doppler, and pulmonary hypertension [139]. Furthermore, National Hospital Discharge Survey data in the period of 1997-2009 showed that SCD is associated with decreased HIV but higher HBV and HCV co-morbidities in adult African-Americans [140].…”
Section: Hiv Infectionsmentioning
confidence: 99%
“…According to Neto et al [ 25 ], HIV infection had no correlation with SCD symptoms; however, a study found that SCD patients had a slower progression of HIV infection into AIDS than their non-SCD counterparts [ 26 ]. Another study showed that SCD patients with HIV face a higher risk of developing SCD complications, despite the fact that it may slow HIV progression and mortality [ 27 ]. Children with SCD and HIV were more likely to suffer from bacterial infections and sepsis than those with SCD alone, and their hospital stays were longer than those without (8.0 days vs. 4.3 days, respectively) [ 28 ].…”
Section: Introductionmentioning
confidence: 99%